Modelling and mitigating software implementation project risks with proposed mining technique - Elzamly, Abdelrafe; Hussin, Burairah (Science and Engineering Publishing Company, 2014)
The aim of this paper is to present new mining technique that uses the fuzzy multiple regression analysis modelling techniques to identify the risk management techniques that are effective in reducing the occurrence of each software implementation risks. Top ten software implementation risk factors and the best thirty risk management techniques were presented to respondents. As a result, we have shown that top ten software implementation risk factors can be reduced by risk management techniques according to mining techniques. This study will guide software managers to apply software risk management practices with real world software development organizations and verify the effectiveness of the new techniques and approaches on a software project. It is hoped that this will enable software managers improve their decision to increase the probability of software project success.